Is septal deviation associated with headache?: A nationwide 10-year follow-up cohort study. Issue 20 (15th May 2020) - Kwon, Sam Hyun; Lee, Eun Jung; Yeo, Cha Dong; Kim, Min Gul; Kim, Jong Seung; Noh, Sang Jae; Kim, Eun Ji; Kim, Su Geun; Lee, Jong-Hwan; Yoo, Ji Seob; Koh, Ji hoon; Kim, Byeong Jin
Abstract : Abstract: To investigate the potential relationship between septal deviation (SD) and headache using nationwide representative cohort sample data. This study used a nationwide cohort sample from the Korean National Health Insurance Service database. The cohort sample was composed of 1 million patients, which is obtained by propensity score matching from 2002 to 2013. There were 9171 individuals in the SD group and 28243 in the control or no SD group. The Kaplan–Meier survival analysis, the log-rank test, and Cox proportional hazard regression analysis were used to calculate the incidence, survival curve, and hazard ratio of headache for each group. There were no statistically significant differences in sex ( P  = .7708), age ( P  = .991), residential area ( P  = .9626), or socioeconomic status ( P  = .9982) between the 2 groups. The survival curve between SD and control or no SD showed a statistically significant difference. The adjusted hazard ratio for headache incidence during the 10-year follow-up period of the SD group was 1.37 (95% CI: 1.31-1.43). This cohort study suggests that SD is associated with headache. Therefore, these findings suggest that septoplasty can be considered as 1 of the treatment option in SD patients with headache.